Vernalization response of wild chickpea - Abbo, S (The New phytologist, 2002)
• Response to low temperature during early growth in cultivated chickpea (Cicer arietinum) and its wild progenitor C. reticulatum was investigated to clarify the evolutionary processes under domestication in this crop. • Parental lines and their F2 and F3 progeny were exposed to cold treatment (4°C) for 30°d after seed imbibition and compared with controls. • Cold treatment caused a 19-d advance in flowering time in wild chickpea, but only a 3-d advance in cultivated chickpea. It also promoted apical dominance of the main stem of the wild chickpea, whereas apical dominance was constitutive in the cultivated type. F3 progeny showed significant genetic variation affecting the response of flowering time to low temperature. We suggest that selection against alleles conferring vernalization requirements was a major step in the evolution of cultivated chickpea. The reduced low-temperature response was fundamental both for the ancient conversion of chickpea from an autumn- to a spring-sown crop ('summer crop') in west Asia, and for its spread into the lower-latitude regions of India and east Africa. • Attempts to improve yield and/or resistance to biotic and abiotic stresses through introgression with wild chickpea species carry the risk of reintroducing vernalization sensitive alleles into the cultigen